2012
DOI: 10.1177/1078155212449031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacy services and research for lymphoma patients at a cancer center

Abstract: At the National Cancer Centre Singapore, which is currently the largest ambulatory cancer centre in Singapore, clinical pharmacists have taken upon responsibilities to provide direct pharmaceutical care in the center’s lymphoma team since 2006. Given the complexity and intricacies of lymphoma treatments, clinical pharmacists are often positioned to ensure supportive care is optimized among these patients. Besides management of chemotherapy-related and supportive care issues, clinical pharmacists play a pivotal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…25 Chan et al reported a 97% acceptability rate for pharmaceutical interventions in an oncology center, close to ours which corresponded to 99.42%. 26 On the other hand, a Brazilian study by Reis et al obtained 76.32% acceptability for interventions carried out in the Adult ICU, Cardiac ICU, and Inpatient Cardiology Clinic Unity. 16 High rates of acceptability show that the clinical staff recognizes the pharmacist as a safe and reliable source of information about drugs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…25 Chan et al reported a 97% acceptability rate for pharmaceutical interventions in an oncology center, close to ours which corresponded to 99.42%. 26 On the other hand, a Brazilian study by Reis et al obtained 76.32% acceptability for interventions carried out in the Adult ICU, Cardiac ICU, and Inpatient Cardiology Clinic Unity. 16 High rates of acceptability show that the clinical staff recognizes the pharmacist as a safe and reliable source of information about drugs.…”
Section: Discussionmentioning
confidence: 98%
“…reported a 97% acceptability rate for pharmaceutical interventions in an oncology center, close to ours which corresponded to 99.42%. 26 On the other hand, a Brazilian study by Reis et al. obtained 76.32% acceptability for interventions carried out in the Adult ICU, Cardiac ICU, and Inpatient Cardiology Clinic Unity.…”
Section: Discussionmentioning
confidence: 98%
“…Asia is a region that is rapidly increasing its provision of clinical pharmacy services, with reports in the literature from China [19][20][21][22], Singapore [23,24], Taiwan [25,26] and Hong Kong [27]. These countries are located in the Western Pacific Region (WPR), which represents one quarter of the world's population ( Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Such prescriptions may include a high number of medications such as chemotherapeutic agents, medications for the alimentary tract and metabolism, nervous system medications, anti‐infective medications for systemic use and blood and hematopoietic organs, and medications for comorbidities unrelated to the cancer. Many of these medications have high potential for drug interactions, dose and frequency adjustments, and adverse side effects, and medication errors may occur (Alshaikh, Mayet, & Aljadhey, ; Chan et al., ; Delpeuch, Leveque, Gourieux, & Herbrecht, ; Koyyalagunta et al., ; Li, Morway, Velasquez, Weingart, & Stuver, ; Stoll & Kopittke, ).…”
Section: Introductionmentioning
confidence: 99%